Blood pages - Bilgere, George, 1951- (Pitt poetry series., 2018)
In Blood Pages George Bilgere continues his exploration of the joys and absurdities of being middle-aged and middle-class in the Midwest. OK, maybe he's a bit beyond middle-aged at this point, and his rueful awareness of this makes these poems even more darkly hilarious, more deeply aware of the feckless and baffling times our nation has stumbled into. And the fact that Bilgere, relatively late in life, is now the father of two young boys brings a fresh sense of urgency to his work. Blood Pages is a guidebook to the fears, foibles, and beauties of our lovely old country as it makes its blundering, tentative way into the new century.